A new species, Henneguya lacustris n. sp. (Cnidaria: Myxosporea), infecting the gills of Astyanax lacustris from Brazil - Vieira, Diego Henrique Mirandola Dias [UNESP] (2020)
The present study describes Henneguya lacustris n. sp. parasitizing Astyanax lacustris (Lütken 1875), from the Tietê River, State of São Paulo, Brazil, through morphological and molecular analysis. Myxospores of the parasites were found in the gills of A. lacustris with 13% prevalence of infection. The myxospores were oval and presented as measures (mean ± standard deviation): total length 18.3 ± 2.2 μm, body length 10.4 ± 1.6 μm, body width 4.9 ± 0.9 μm, tail length 7.2 ± 2.5 μm. The polar capsule was 4.8 ± 0.3 μm long and 1.5 ± 0.2 μm wide. The polar tubules, present inside the polar capsules, had 6 to 7 turns. The ultrastructural analysis allowed the observation of the asynchronous development of the myxospores. Phylogenetic analysis showed H. lacustris n. sp. as a sister species of H. chydadea Barassa and Cordeiro 2003 in a subclade formed by species that parasitize the gills of Characiform fish from Brazil. Using molecular and morphological characterization, this parasite was identified as a new species of the genus Henneguya Thélohan 1892.